Boleče in pekoče noge - Meh, Duška (Obzornik zdravstvene nege, 1998)
Peripheral neuropathy is a frequent impariment of peripheral nerves, repeatedly affects only the sensitivity. Electrophysiological examination (elektomyography and electroneugraphy) frequently revealed no abnormality. Thenew psychophysical (thermotest, vibrameter, algometer...) and electrophysiologic tests of autonomic functions detect abnormality of small nerve fibres, which are domaged in those patients. In the article, assessment of thermal specific and thermal pain sensitivity is described.
Keywords: bolečina; Cold; etiologija; Foot; nevropatije; noge; Pain; Pain threshold; periferno živčevje; Peripheral nervous system diseases